THE ANALYSIS OF TRANSLATION TECHNIQUES IN TRANSLATING AHMAD FUADI’S NEGERI 5 MENARA INTO ANGIE KILBANE’S THE LAND OF 5 TOWERS - Rahmaningsih, Nanda; Hutahaean, Sorta (Jurnal Ilmu Budaya, 2021)
This research is about The Analysis of Translation Techniques in Translating Ahmad Fuadi’s Negeri 5 Menara into Angie Kilbane’s The Land of 5 Towers. This analysis is library research and applying the descriptive method. From the analysis, it found out that the translator applies all of eighteen techniques translation by Molina and Albir, they are: Pure Borrowing with 23 data. Naturalized Borrowing with 17 data. Calque with 13 data. Literal Translation with 17 data. Compensation with 4 data. Transposition with 27 data. Description with 9 data. Modulation with 69 data. Amplification with 18 data. Adaptation with 33 data. Established Equivalent with 6 data. Generalization with 17 data. Particularization with 4 data. Reduction with 22 data. Discursive Creation with 2 data. Substitution, Linguistic Compression, and Linguistic Amplification with 5 data. Variation with 7 data. The most dominant technique used is Modulation with 69 data, while the most less technique used is Discursive Creation with 2 data.